Do Business Cycles Have Long-Term Impact for Particular Cohorts? - Torben M Andersen; Jonas Maibom Pedersen; Michael Svarer; Allan Sørensen (Institute for the Study of Labor (IZA), 2013)
Will the current employment crisis produce lost generations with permanently lower labour market attachment? Taking an explicit cohort perspective and based on Danish data we do not find strong persistence in employment rates at the cohort level. Younger workers tend to be more exposed to business cycle fluctuations than older workers, but importantly they recover more quickly from such set-backs than older workers for whom persistence is stronger. Moreover, no cohorts have been disproportionately affected by exposure to a sequence of adverse shocks. An explicit account of overlapping cohorts is shown to affect assessments of persistence in aggregate employment rates.
Keywords: J6; E32; 330; persistence; lost generations; employment